2003
DOI: 10.1148/rg.234025044
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Obliteration of Gastric Varices

Abstract: Since its introduction in the mid-1990s, balloon-occluded retrograde transvenous obliteration (BRTO) has become widely accepted in Japan as a minimally invasive, highly effective treatment for gastric varices. Sufficient filling and stagnation of the sclerosing agent in the entire variceal complex is essential for successful BRTO of gastric varices. However, the success of BRTO in this context also requires familiarity with the hemodynamic features of the varices, including the patterns of their afferent and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
116
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 17 publications
0
116
0
3
Order By: Relevance
“…Especially in the case of Hirota's grade 3 or 4 varices, 21 additional specialized techniques to treat minor collaterals were utilized. 15,18,21,23,28,30,39,40 If occlusion of minor collateral vessels was necessary, a 50% glucose solution, ethanol, and embolic coils were used. With or without these interventions, a 2.8-French microcatheter (Rapid transit; Johnson and Johnson, New Brunswick, NJ, USA) was introduced through a balloon catheter to the gastric varices, and 2.5-5 ml of 5% ethanolamine oleate was injected intermittently into the gastric varices under fl uoroscopy (Fig.…”
Section: Balloon-occluded Retrograde Transvenous Obliterationmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in the case of Hirota's grade 3 or 4 varices, 21 additional specialized techniques to treat minor collaterals were utilized. 15,18,21,23,28,30,39,40 If occlusion of minor collateral vessels was necessary, a 50% glucose solution, ethanol, and embolic coils were used. With or without these interventions, a 2.8-French microcatheter (Rapid transit; Johnson and Johnson, New Brunswick, NJ, USA) was introduced through a balloon catheter to the gastric varices, and 2.5-5 ml of 5% ethanolamine oleate was injected intermittently into the gastric varices under fl uoroscopy (Fig.…”
Section: Balloon-occluded Retrograde Transvenous Obliterationmentioning
confidence: 99%
“…3,17,18 If a large spontaneous shunt is present and the portal pressure gradient (as measured by hepatic vein wedge pressure gradient) is <12 mmHg, B-RTO should be considered. 19 However, the majority of reports in the literature pertain to prophylactic treatment, and the long-term outcome after B- RTO has not yet been fully demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the success of BRTO under these circumstances requires familiarity with the patterns of the variceal afferent and draining veins. 19 In this case, venography revealed an afferent vein from the splenic vein and another from the inferior mesenteric vein, and draining veins into the left superfi cial epigastric vein. We decided to perform the BRTO procedure for this case, because BRTO is similar to but less invasive than PTO.…”
mentioning
confidence: 65%
“…Gastric varices can be classified according to the afferent veins (Type 1 to 3) or the draining veins (Type A to D) [3,4]. Type 1 gastric varices are typified by a single afferent gastric vein whilst Type 2, by multiple afferent gastric veins.…”
Section: Discussionmentioning
confidence: 99%
“…In Type B varices, the outcome of BRTO depends on the number, size and ease by which the collateral draining veins can be occluded. [4] Yamagami et al [6] recently showed that embolisation of collateral veins from gastric varices prior to BRTO is a safe and useful procedure, although they noted that gastric varices with collaterals sufficiently large to necessitate embolisation may require careful follow-up for recurrence. In cases where there are high-flow or large number of draining veins which cannot be occluded, the injected sclerosant will flow into the systemic veins, leading to reduced efficacy of BRTO.…”
Section: Discussionmentioning
confidence: 99%